A Multi-Omics Study of Familial Lung Cancer: Microbiome and Host Gene Expression Patterns - Chen, Ying; Huang, Yunchao; Ding, Xiaojie; Yang, Zhenlin; He, Liang; Ning, Mingjie; Yang, Zhenghong; He, Daqian; Yang, Lijuan; Liu, Zhangyi; Chen, Yan; Li, Guangjian (Frontiers in Immunology, 2022)
Background: Inherited susceptibility and environmental carcinogens are crucial players in lung cancer etiology. Lung microbiome is getting rising attention in carcinogenesis. Present work was to investigate the microbiome in lung cancer patients, affected by familial lung cancer (FLC) and indoor air pollution (IAP); further, compare host gene expression patterns with their microbiome for potential links. Methods: Tissue sample pairs (cancer and adjacent nonmalignant tissue) were used for 16S rRNA (microbiome) and RNA-seq (host gene expression). Subgroup microbiome diversities and their matched gene expression patterns were analyzed. Significantly enriched taxa were screened out, based on different clinicopathologic characteristics. Results: FLC microbiome seemed to be smaller, low-diversity and inactive to change; we noted microbiome difference in gender, age, blood type, anatomy site, histology type, TNM stage as well as IAP and smoking conditions. We also found smoking and IAP dramatically decreased specific-OTU biodiversity, especially in normal lung tissue. Intriguingly, enriched microbes were in 3 categories: opportunistic pathogens, probiotics and pollutants-detoxication microbes; the 3rd involved: Sphingomonas, Sphingopyxis etc. which helping degrade pollutants, while may also cause epithelial damage and chronic inflammation. RNA-seq highlighted IL17, Ras, MAPK and Notch pathways, which associated with carcinogenesis and compromised immune system. Conclusions: Lung microbiome can play vital roles in carcinogenesis. FLC and IAP subjects were affected by fragile lung epithelium, vulnerable host-microbes equilibrium and dysregulated immune surveillance & response. Our findings provided useful information to study the triple interplay among environmental carcinogens, population genetic background and diversified lung microbiome.